Taekwondo win-loss determining factors using data mining-based decision tree analysis: focusing on game analysis for evidence-based coaching - Jeon, M.; Lim, H. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Purpose In this study, the purpose of this study is to identify the determinants of winning and losing in taekwondo by applying decision tree analysis, one of the data mining techniques, based on the 2022 World taekwondo championships women`s competition.